Development of a Milk Based Condensed Curd - Jayasinghe, W.D.M.N.I.; Rikkas, F.R.; Thanusan, S. (University of Jaffna, 2023)
The dairy sector requires value added and quality enhanced dairy products. Therefore, this study was conducted to develop a value added condensed curd from fresh milk. There were 20 undergraduates (semi-trained panelists) used to evaluate the product sensory characteristics using the descriptive analysis method. Acceptability of the prepared sweetened buffalo curd (T1) and cow milk curd (T2), were evaluated sensorily (ST1) compared to the traditional cow milk curd (T3). Accordingly, T1 was the most preferred (p<0.05) curd. Sugar levels: very low (L1), low (L2), medium (L3), and high (L4) were tested sensorily (ST2) in T1 to identify the most preferred sweetness level, which was L3. Third sensory test (ST3), was conducted using T1L3 to check the most preferred texture due to three condensation levels of fresh milk; low (C1), medium (C2), and high (C3), where C2 had the most preferred texture. The non flavoured curd was sensorily much preferred than the flavoured curd with strawberry (V1), vanilla (V2), and chocolate (V3) flavours. According to the proximate analysis, the most preferred curd contained 5.1% ± 0.4%, protein, 4.4% ± 0.2% fat, 126.3 kcal/100g energy, 0.1 %( ±0.05% Ca) and 71.4% ± 1.2% moisture. The shelf life of the T1L3C2 was over 14 days under refrigerated conditions with titratable acidity 0.83%. The shelf life was extended over 28 days with a titradable acidity of 0.85% under refrigerated conditions by adding Potassium sorbate as the preservative. The market survey conducted on the new product using 300 undergraduates (untrained panalists) at the university premises revealed that a sweetened condensed curd with non flavor, a medium level of sweetness and condensation that can be successfully prepared by buffalo milk was the most acceptable condensed sweet curd for dairy customers.
Keywords: Buffalo milk; Dairy products; Sweet curd; Sensory analysis